The Product Strategy of Afterwork Study at Masjid Al Lathiif Bandung : A Case Study - Syauqi, Rasyid Ilyasa; Herma Musyanto, Moch. (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2023)
Abstract: Masjid Al Lathiif in Bandung is actively involved in religious and educational activities. The regular program called